INFLUENCE BURDEN WORK AND COMPENSATION THE RELATIONSHIP OF THE DESIRED TO CHANGE JOBS WITH JOB SATISFACTION AS AN INTERVENING VARIABLE IN BEAUTY ADVISORS AZZURA PT. INDOSAKTI MEDAN - Amelia Koto; Lenny Menara Sari Saragih (RADJA PUBLIKA, 2026)
This study aims to determine the effect of workload and compensation on turnover intention with job satisfaction as an intervening variable. The research method used is quantitative, with questionnaires as the data collection instrument. Data analysis was carried out using path analysis, t-test, determination test, and Sobel test. The research sample consisted of Beauty Advisor employees at Azzura PT. Indosakti Medan. The results of the study show that workload has a positive and significant effect on job satisfaction, as well as a positive and significant effect on turnover intention. Compensation has a positive but insignificant effect on job satisfaction, but a negative and significant effect on turnover intention. Job satisfaction is proven to have a negative and significant effect on turnover intention. The Sobel test results indicate that job satisfaction is not able to serve as an intervening variable in the effect of workload and compensation on turnover intention.